271. US Hospitalizations and 60-Day Readmission Rates Associated with Herpes Simplex Virus Encephalitis. (4th December 2021) - Hansen, Michael; Hasbun, Rodrigo; Hasbun, Rodrigo
Abstract: Background: Herpes Simplex encephalitis (HSE) is the most common cause of encephalitis hospitalizations with a known etiology. However, it remains a challenge to capture a comprehensive and robust understanding of the disease, particularly for long term outcomes after acute diagnosis and treatment. In particular, there is a growing body of literature showing increased concern for recurrent encephalopathic disease several weeks after initial HSE recovery. We sought to describe and analyze features associated with all cause readmissions and encephalopathy associated readmissions amongst HSE cases. Methods: HSE hospitalizations and 60-day rehospitalizations were assessed in a retrospective cohort using linked hospitalizations from the Healthcare Utilization Project (HCUP) National Readmission Database (NRD) from 2010 through 2017. Risk factors for all-cause readmissions and encephalopathy associated readmissions were assessed with a weighted logistic regression model. Results: There were 10, 272 HSE cases in the United States between 2010 and 2017, resulting in a national rate of 4.95 per 100, 000 hospitalizations. A total of 23.7% were readmitted at least once within 60-days. Patients that were readmitted were older (mean age 62.4 vs. 57.9, p< 0.0001), had a greater number of procedures at the index hospitalization (aOR 1.03, p< 0.0001) and have a higher Charlson comorbidity score (aOR 1.11, p< 0.0001). Amongst those readmitted, 465 (16.5%) had an encephalopathy related diagnosis. Over eight years, the prevalence of encephalopathy associated readmissions increased from 0.12 to 0.20 (figure 1). Encephalopathy specific readmissions were found to be associated with greater age (mean age 6.9 vs. 61.7, p = 0.004) and findings of cerebral edema at index hospitalization (aOR 2.16, p < 0.0001). Most Common Diagnosis Groups Listed at the 60-Day Readmission Conclusion: HSE 60-day readmissions are relatively common, particularly among older and sicker individuals. Readmissions were often associated with new neurological symptoms concerning for either recurrent or new encephalopathic events. Early signs and symptoms of neurological disease at index were correlated with encephalopathic specific readmissions. Disclosures: Rodrigo Hasbun, MD, MPH, Biofire (Speaker's Bureau) Rodrigo Hasbun, MD, MPH, Biofire (Individual(s) Involved: Self): Consultant, Research Grant or Support